Distribution and Size of Crab (Portunus pelagicus) in Betahwalang Waters, Demak, Central JavaSex Ratio, Size Distribution and Length-Weight Relationship of Portunus pelagicus Linnaeus, 1758 (Malacostraca : Portunidae) in Betahwalang, Demak, Central Java - Sri Redjeki; Muhammad Zainuri; Ita Widowati; Ambariyanto Ambariyanto; Rudhi Pribadi; Michael Abbey (Universitas Diponegoro, 2021)
Blue Swimming Crab (P. pelagicus, Linnaeus, 1758) is the main fisheries product from Betahwalang peoples. Fishing activity of Blue Swimming Crab by the fisherman almost every day in Betahwalang waters. Distribution and body size data of Blue Swimming Crab can be used for sustain management reference. The purpose of this study was to determine distribution pattern and body size of Blue Swimming Crab, started from July to November 2018 in Betahwalang waters, Demak. The data analyze consist of sex ratio, carapace width distribution and relationship between carapace width and body weight. 11790 samples Blue Swimming crab from Betahwalang waters consist of 7070 female crabs and 4720 male crabs. The result showed that sex-ratio between male and female crabs are balanced (1.0:1.37), with the most female crabs found at July and August. Body size distribution of male and female crabs are dominated in class 103-111 mm carapace width. Male and female crabs have a positive allometric on growth parameters, that means growth of the body weight is faster than carapace width. The result showed that Blue Swimming Crab in Betahwalang waters are support for sustainable fisheries.